The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1161/01.cir.69.4.766
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cardioversion/defibrillation thresholds in man by a truncated exponential waveform and an apical patch-superior vena caval spring electrode configuration.

Abstract: Defibrillation/cardioversion thresholds were measured in 33 patients undergoing defibrillator implants. Each patient had a 12 cm2 patch placed near the left ventricular apex via a thoracotomy and a 10 cm2 spring lead placed pervenously at the right atrial-superior vena caval junction. Ventricular tachycardia of stable morphology, polymorphic ventricular tachycardia, or ventricular fibrillation was induced four times in each patient and 1, 5, 10, and 25 J truncated exponential shocks with 60% tilt were given in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…The study by Kerber et al (16) demonstrated that the degree of organization of ventricular tachyarrhythmia determines the energy and current requirements for successful transthoracic cardioversion and defibrillation. Similar were the conclusions by Winkle et al (28), which were derived from their internal defibrillation studies. However, the mechanisms by which the organization of the arrhythmia affects the probability of success for a given shock strength remain unclear.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The study by Kerber et al (16) demonstrated that the degree of organization of ventricular tachyarrhythmia determines the energy and current requirements for successful transthoracic cardioversion and defibrillation. Similar were the conclusions by Winkle et al (28), which were derived from their internal defibrillation studies. However, the mechanisms by which the organization of the arrhythmia affects the probability of success for a given shock strength remain unclear.…”
supporting
confidence: 88%
“…Cardioversion of a monomorphic ventricular tachycardia (VT) typically requires less energy than termination of ventricular fibrillation (VF). The American Heart Association recommends using lower currents and energies for termination of VT (1); these recommendations are supported by clinical studies (16,28). The study by Kerber et al (16) demonstrated that the degree of organization of ventricular tachyarrhythmia determines the energy and current requirements for successful transthoracic cardioversion and defibrillation.…”
mentioning
confidence: 99%
“…Testing included the induction and termination of ventricular fibrillation in patients who have experienced ventricular tachycardia only clinically, since there is an unavoidable incidence of ventricular tachycardia acceleration even with R wave synchronous pulse discharges. 8 We also prefer that an arrhythmia be terminated with the initial pulse discharge rather than by one of the three subsequent backup discharges. This extensive testing with optimization of electrode configuration may also contribute to the high survival rates in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular tachycardia is generally more easily terminated with lower energy shocks than is ventricular fibrillation. 13 Our data should not be extrapolated beyond the 15-second duration of ventricular fibrillation that we evaluated. The difference in defibrillation efficacy between 5 and 15 seconds seen only at 300 V in this study could possibly be observed at higher energies if the duration of fibrillation is longer than 15 seconds.…”
mentioning
confidence: 97%